1933
DOI: 10.1002/andp.19334090806
|View full text |Cite
|
Sign up to set email alerts
|

Über flüssige Metalleinkristalle. I

Abstract: E. Donat u. 0. Stierstadt. Uber fliissige Metalleiiikristalle. I 897 Uber fliissiye Metalleinkristalle. I Von E. Domat and 0. S t i e r s t a d t (Mit 7 Figuren) I n h a l t : Es wird der Zustand geschmolzener Bi-Einkristalle unmittelbur iiber dem Schmelzpunkt im Hinblick anf eine kristalline Struktur der Schmelze untersucht. Kine solche kommt in elektrischen Leitfghigkeitsmessungcn direkt nicht zum Ausdruck. Das Kristallisationsverhalten hingegen weist darauf hin, daB der Schmelze selbst eine kristalline Stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1933
1933
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Earlier [22] and later [23] work by other researchers showed that the orientation of melted Bi single-crystals affected the measured thermoelectric power of the melt up to 8 degrees above the melting point. Additionally, the possibility of melting and resolidifying bismuth without loss of memory of the orientation was corroborated by others [24]. Nevertheless, it seems that these experimental findings were hardly, if at all, referred to after the second world war.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Earlier [22] and later [23] work by other researchers showed that the orientation of melted Bi single-crystals affected the measured thermoelectric power of the melt up to 8 degrees above the melting point. Additionally, the possibility of melting and resolidifying bismuth without loss of memory of the orientation was corroborated by others [24]. Nevertheless, it seems that these experimental findings were hardly, if at all, referred to after the second world war.…”
mentioning
confidence: 62%
“…Additionally, the possibility of melting and resolidifying Bismuth without loss of memory of the orientation was corroborated by others. 19 Nevertheless, it seems that these experimental findings were hardly, if at all, referred to after the second world war.…”
mentioning
confidence: 96%
See 1 more Smart Citation